Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

No hiding behind trees: navigating the gap between forest carbon removal potential and urgent climate mitigation - Yifan Xu; Yijie Wang; Philippe Ciais; Pete Smith; Wenping Yuan; Josep G. Canadell; Zhangcai Qin (Science Bulletin, 2026)

Underestimation of Future Agricultural Soil N 2 O Emissions and Abatement Needs - Chaoqun Lu; Linchao Li; Wilfried Winiwarter; Josep G. Canadell; Weihang Liu; Hanqin Tian (Global Change Biology, 2026)
Agricultural soils are the largest human‐induced source of nitrous oxide (N 2 O) due to the extensive fertilizer use in crop production. Despite progress made in global N 2 O budget accounting, using the IPCC‐derived static emission factors (EF) limits our capability to project future changes in agricultural N 2 O emissions and identify cost‐effective mitigation strategies. Here, we use a physics‐informed AI‐driven dynamic EF modeling framework to project direct agricultural soil N 2 O emissions induced by mineral fertilizer additions under various climate and nitrogen (N) regulation policy scenarios. Compared to projections based on static EF, our study yields higher future N 2 O emissions by 0.3–1.1 Tg N year −1 across scenarios by 2050, implying greater abatement needs to combat climate change. The gap between static and dynamic EF approaches is projected to widen to 29%–34% by mid‐century. Under moderate‐ to high‐ambition N regulation policies, we project that a 25% emission reduction can be reached before 2050, while a 45% reduction is only attainable under high‐ambition N policies and strong climate action. The potential for N 2 O mitigation due to a policy shift varies substantially among regions, with seven top source regions contributing 76%–87% of global N 2 O reduction. Adopting N 2 O reduction technologies in hotspot areas would significantly accelerate the timeline for achieving the 25% reduction goal. Improving fertilizer management on croplands can provide climate benefits comparable to, or even exceeding, those of enhancing soil carbon sequestration, particularly in regions with low nitrogen use efficiency. Our findings highlight the higher mitigation potential of targeting N 2 O emission hotpots and the urgency of implementing policy shifts.

Strong and Rapid Postfire Recovery of Vegetation Productivity in Australia - Li Pan; Xiangming Xiao; Yuanwei Qin; Josep G. Canadell; Alfredo Huete; Philippe Ciais; Shenglai Yin; Chenchen Zhang; Baihong Pan; Chenglong Yin; Cheng Meng; Yuan Yao; et al. (Global Change Biology, 2025)
Fires disrupt ecosystems, release carbon, and reduce carbon uptake, which increases atmospheric CO 2 concentration, warms the atmosphere, and fosters more frequent and intense fires. Quantifying postfire recovery is crucial for understanding the adaptability and resilience of ecosystems to fire disturbances. Observations from satellite‐derived active fire (~1‐km) and Gross Primary Productivity (GPP) products reveal that Australia experiences extensive fires annually, reducing vegetation productivity. Here we analyze the post‐fire GPP recovery trajectories of 1.7 × 10 6 fire‐affected pixels (or 1.5 × 10 6 km 2 ) in Australia between 2011 and 2019, of which 1.3 × 10 6 pixels (1.2 × 10 6 km 2 ) experienced a single fire (single‐fire pixels), and 0.4 × 10 6 pixels (0.3 × 10 6 km 2 ) experienced two or more fires (multiple‐fire pixels). We found that Australia's postfire GPP recovery was strong and rapid. 88% of single‐fire pixels recovered to 135% of the prefire level in an average of 2.3 years, whereas 86% of multiple‐fire pixels recovered to 115% of the prefire level in an average of 1.2 years. NonForest ecosystems (e.g., grasslands, shrublands, and savannas) exhibited a higher postfire recovery magnitude (138% for single‐fire pixels and 115% for multiple‐fire pixels) compared to Forest (110% for single‐fire pixels and 108% for multiple‐fire pixels). This rapid and robust postfire GPP recovery is significantly influenced by postfire precipitation, fire (i.e., fire frequency, intensity) and fire severity (damage, impacts; a metric of resistance of terrestrial ecosystems to fire). Specifically, higher fire severity and higher postfire precipitation have a positive impact on postfire recovery, whereas increased fire frequency has a negative impact. Furthermore, fire dynamics have a smaller role in the long‐term interannual continental GPP changes than climate or land‐use changes, as strong and rapid GPP recovery offsets the short‐term fire‐induced GPP losses.

Enhanced nitrous oxide emission factors due to climate change increase the mitigation challenge in the agricultural sector - Linchao Li; Chaoqun Lu; Wilfried Winiwarter; Hanqin Tian; Josep G. Canadell; Akihiko Ito; Atul K. Jain; Sian Kou‐Giesbrecht; Shufen Pan; Naiqing Pan; Hao Shi; Qing Sun; et al. (Global Change Biology, 2024)
Effective nitrogen fertilizer management is crucial for reducing nitrous oxide (N 2 O) emissions while ensuring food security within planetary boundaries. However, climate change might also interact with management practices to alter N 2 O emission and emission factors (EFs), adding further uncertainties to estimating mitigation potentials. Here, we developed a new hybrid modeling framework that integrates a machine learning model with an ensemble of eight process‐based models to project EFs under different climate and nitrogen policy scenarios. Our findings reveal that EFs are dynamically modulated by environmental changes, including climate, soil properties, and nitrogen management practices. Under low‐ambition nitrogen regulation policies, EF would increase from 1.18%–1.22% in 2010 to 1.27%–1.34% by 2050, representing a relative increase of 4.4%–11.4% and exceeding the IPCC tier‐1 EF of 1%. This trend is particularly pronounced in tropical and subtropical regions with high nitrogen inputs, where EFs could increase by 0.14%–0.35% (relative increase of 11.9%–17%). In contrast, high‐ambition policies have the potential to mitigate the increases in EF caused by climate change, possibly leading to slight decreases in EFs. Furthermore, our results demonstrate that global EFs are expected to continue rising due to warming and regional drying–wetting cycles, even in the absence of changes in nitrogen management practices. This asymmetrical influence of nitrogen fertilizers on EFs, driven by climate change, underscores the urgent need for immediate N 2 O emission reductions and further assessments of mitigation potentials. This hybrid modeling framework offers a computationally efficient approach to projecting future N 2 O emissions across various climate, soil, and nitrogen management scenarios, facilitating socio‐economic assessments and policy‐making efforts.

Global nitrous oxide emissions from livestock manure during 1890–2020: An IPCC tier 2 inventory - Lei Zhang; Shufen Pan; Zhiyun Ouyang; Josep G. Canadell; Jinfeng Chang; Giulia Conchedda; Eric A. Davidson; Fei Lu; Naiqing Pan; Xiaoyu Qin; Hao Shi; Francesco N. Tubiello; et al. (Global Change Biology, 2024)
Nitrous oxide (N 2 O) emissions from livestock manure contribute significantly to the growth of atmospheric N 2 O, a powerful greenhouse gas and dominant ozone‐depleting substance. Here, we estimate global N 2 O emissions from livestock manure during 1890–2020 using the tier 2 approach of the 2019 Refinement to the 2006 IPCC Guidelines. Global N 2 O emissions from livestock manure increased by ~350% from 451 [368–556] Gg N year −1 in 1890 to 2042 [1677–2514] Gg N year −1 in 2020. These emissions contributed ~30% to the global anthropogenic N 2 O emissions in the decade 2010–2019. Cattle contributed the most (60%) to the increase, followed by poultry (19%), pigs (15%), and sheep and goats (6%). Regionally, South Asia, Africa, and Latin America dominated the growth in global emissions since the 1990s. Nationally, the largest emissions were found in India (329 Gg N year −1 ), followed by China (267 Gg N year −1 ), the United States (163 Gg N year −1 ), Brazil (129 Gg N year −1 ) and Pakistan (102 Gg N year −1 ) in the 2010s. We found a substantial impact of livestock productivity, specifically animal body weight and milk yield, on the emission trends. Furthermore, a large spread existed among different methodologies in estimates of global N 2 O emission from livestock manure, with our results 20%–25% lower than those based on the 2006 IPCC Guidelines. This study highlights the need for robust time‐variant model parameterization and continuous improvement of emissions factors to enhance the precision of emission inventories. Additionally, urgent mitigation is required, as all available inventories indicate a rapid increase in global N 2 O emissions from livestock manure in recent decades.

Future hotter summer greatly increases residential electricity consumption in Beijing: A study based on different house layouts and shared socioeconomic pathways - Qiyuan Hu; Jiayue Tang; Xiang Gao; Sijia Wang; Dan Zhang; Yuting Qin; Qihan Wang; Yi Zhou; Na Huang; Josep Penuelas; Jordi Sardans; Josep G. Canadell; et al. (Sustainable Cities and Society, 2023)

A 130‐year global inventory of methane emissions from livestock: Trends, patterns, and drivers - Lei Zhang; Hanqin Tian; Hao Shi; Shufen Pan; Jinfeng Chang; Shree R. S. Dangal; Xiaoyu Qin; Siyuan Wang; Francesco N. Tubiello; Josep G. Canadell; Robert B. Jackson (Global Change Biology, 2022)
Livestock contributes approximately one‐third of global anthropogenic methane (CH 4 ) emissions. Quantifying the spatial and temporal variations of these emissions is crucial for climate change mitigation. Although country‐level information is reported regularly through national inventories and global databases, spatially explicit quantification of century‐long dynamics of CH 4 emissions from livestock has been poorly investigated. Using the Tier 2 method adopted from the 2019 Refinement to 2006 IPCC guidelines, we estimated CH 4 emissions from global livestock at a spatial resolution of 0.083° (~9 km at the equator) during the period 1890–2019. We find that global CH 4 emissions from livestock increased from 31.8 [26.5–37.1] (mean [minimum−maximum of 95% confidence interval) Tg CH 4 yr −1 in 1890 to 131.7 [109.6–153.7] Tg CH 4 yr −1 in 2019, a fourfold increase in the past 130 years. The growth in global CH 4 emissions mostly occurred after 1950 and was mainly attributed to the cattle sector. Our estimate shows faster growth in livestock CH 4 emissions as compared to the previous Tier 1 estimates and is ~20% higher than the estimate from FAOSTAT for the year 2019. Regionally, South Asia, Brazil, North Africa, China, the United States, Western Europe, and Equatorial Africa shared the majority of the global emissions in the 2010s. South Asia, tropical Africa, and Brazil have dominated the growth in global CH 4 emissions from livestock in the recent three decades. Changes in livestock CH 4 emissions were primarily associated with changes in population and national income and were also affected by the policy, diet shifts, livestock productivity improvement, and international trade. The new geospatial information on the magnitude and trends of livestock CH 4 emissions identifies emission hotspots and spatial–temporal patterns, which will help to guide meaningful CH 4 mitigation practices in the livestock sector at both local and global scales.

Regional trends and drivers of the global methane budget - Ann R. Stavert; Marielle Saunois; Josep G. Canadell; Benjamin Poulter; Robert B. Jackson; Pierre Regnier; Ronny Lauerwald; Peter A. Raymond; George H. Allen; Prabir K. Patra; Peter Bergamaschi; Phillipe Bousquet; et al. (Global Change Biology, 2022)
The ongoing development of the Global Carbon Project (GCP) global methane (CH 4 ) budget shows a continuation of increasing CH 4 emissions and CH 4 accumulation in the atmosphere during 2000–2017. Here, we decompose the global budget into 19 regions (18 land and 1 oceanic) and five key source sectors to spatially attribute the observed global trends. A comparison of top‐down (TD) (atmospheric and transport model‐based) and bottom‐up (BU) (inventory‐ and process model‐based) CH 4 emission estimates demonstrates robust temporal trends with CH 4 emissions increasing in 16 of the 19 regions. Five regions—China, Southeast Asia, USA, South Asia, and Brazil—account for >40% of the global total emissions (their anthropogenic and natural sources together totaling >270 Tg CH 4 yr −1 in 2008–2017). Two of these regions, China and South Asia, emit predominantly anthropogenic emissions (>75%) and together emit more than 25% of global anthropogenic emissions. China and the Middle East show the largest increases in total emission rates over the 2000 to 2017 period with regional emissions increasing by >20%. In contrast, Europe and Korea and Japan show a steady decline in CH 4 emission rates, with total emissions decreasing by ~10% between 2000 and 2017. Coal mining, waste (predominantly solid waste disposal) and livestock (especially enteric fermentation) are dominant drivers of observed emissions increases while declines appear driven by a combination of waste and fossil emission reductions. As such, together these sectors present the greatest risks of further increasing the atmospheric CH 4 burden and the greatest opportunities for greenhouse gas abatement.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Climate drives global soil carbon sequestration and crop yield changes under conservation agriculture - Wenjuan Sun; Josep G. Canadell; Lijun Yu; Lingfei Yu; Wen Zhang; Pete Smith; Tony Fischer; Yao Huang (Global Change Biology, 2020)
Conservation agriculture has been shown to have multiple benefits for soils, crop yield and the environment, and consequently, no‐till, the central practice of conservation agriculture, has rapidly expanded. However, studies show that the potential for carbon (C) sequestration in no‐till farming sometimes is not realized, let alone the ability to maintain or improve crop yield. Here we present a global analysis of no‐till‐induced changes of soil C and crop yield based on 260 and 1,970 paired studies; respectively. We show that, relative to local conventional tillage, arid regions can benefit the most from conservation agriculture by achieving a win‐win outcome of enhanced C sequestration and increased crop yield. However, more humid regions are more likely to increase SOC only, while some colder regions have yield losses and soil C loss as likely as soil C gains. In addition to site‐specific characteristics and management, a careful assessment of the regional climate is needed to determine the potential benefits of adopting conservation agriculture.

Higher than expected CO 2 fertilization inferred from leaf to global observations - Vanessa Haverd; Benjamin Smith; Josep G. Canadell; Matthias Cuntz; Sara Mikaloff‐Fletcher; Graham Farquhar; William Woodgate; Peter R. Briggs; Cathy M. Trudinger (Global Change Biology, 2020)
Several lines of evidence point to an increase in the activity of the terrestrial biosphere over recent decades, impacting the global net land carbon sink (NLS) and its control on the growth of atmospheric carbon dioxide ( c a ). Global terrestrial gross primary production (GPP)—the rate of carbon fixation by photosynthesis—is estimated to have risen by (31 ± 5)% since 1900, but the relative contributions of different putative drivers to this increase are not well known. Here we identify the rising atmospheric CO 2 concentration as the dominant driver. We reconcile leaf‐level and global atmospheric constraints on trends in modeled biospheric activity to reveal a global CO 2 fertilization effect on photosynthesis of 30% since 1900, or 47% for a doubling of c a above the pre‐industrial level. Our historic value is nearly twice as high as current estimates (17 ± 4)% that do not use the full range of available constraints. Consequently, under a future low‐emission scenario, we project a land carbon sink (174 PgC, 2006–2099) that is 57 PgC larger than if a lower CO 2 fertilization effect comparable with current estimates is assumed. These findings suggest a larger beneficial role of the land carbon sink in modulating future excess anthropogenic CO 2 consistent with the target of the Paris Agreement to stay below 2°C warming, and underscore the importance of preserving terrestrial carbon sinks.

State of the science in reconciling top‐down and bottom‐up approaches for terrestrial CO 2 budget - Masayuki Kondo; Prabir K. Patra; Stephen Sitch; Pierre Friedlingstein; Benjamin Poulter; Frederic Chevallier; Philippe Ciais; Josep G. Canadell; Ana Bastos; Ronny Lauerwald; Leonardo Calle; Kazuhito Ichii; et al. (Global Change Biology, 2020)
Robust estimates of CO 2 budget, CO 2 exchanged between the atmosphere and terrestrial biosphere, are necessary to better understand the role of the terrestrial biosphere in mitigating anthropogenic CO 2 emissions. Over the past decade, this field of research has advanced through understanding of the differences and similarities of two fundamentally different approaches: “top‐down” atmospheric inversions and “bottom‐up” biosphere models. Since the first studies were undertaken, these approaches have shown an increasing level of agreement, but disagreements in some regions still persist, in part because they do not estimate the same quantity of atmosphere–biosphere CO 2 exchange. Here, we conducted a thorough comparison of CO 2 budgets at multiple scales and from multiple methods to assess the current state of the science in estimating CO 2 budgets. Our set of atmospheric inversions and biosphere models, which were adjusted for a consistent flux definition, showed a high level of agreement for global and hemispheric CO 2 budgets in the 2000s. Regionally, improved agreement in CO 2 budgets was notable for North America and Southeast Asia. However, large gaps between the two methods remained in East Asia and South America. In other regions, Europe, boreal Asia, Africa, South Asia, and Oceania, it was difficult to determine whether those regions act as a net sink or source because of the large spread in estimates from atmospheric inversions. These results highlight two research directions to improve the robustness of CO 2 budgets: (a) to increase representation of processes in biosphere models that could contribute to fill the budget gaps, such as forest regrowth and forest degradation; and (b) to reduce sink–source compensation between regions (dipoles) in atmospheric inversion so that their estimates become more comparable. Advancements on both research areas will increase the level of agreement between the top‐down and bottom‐up approaches and yield more robust knowledge of regional CO 2 budgets.

Interannual variation of terrestrial carbon cycle: Issues and perspectives - Shilong Piao; Xuhui Wang; Kai Wang; Xiangyi Li; Ana Bastos; Josep G. Canadell; Philippe Ciais; Pierre Friedlingstein; Stephen Sitch (Global Change Biology, 2020)
With accumulation of carbon cycle observations and model developments over the past decades, exploring interannual variation (IAV) of terrestrial carbon cycle offers the opportunity to better understand climate–carbon cycle relationships. However, despite growing research interest, uncertainties remain on some fundamental issues, such as the contributions of different regions, constituent fluxes and climatic factors to carbon cycle IAV. Here we overviewed the literature on carbon cycle IAV about current understanding of these issues. Observations and models of the carbon cycle unanimously show the dominance of tropical land ecosystems to the signal of global carbon cycle IAV, where tropical semiarid ecosystems contribute as much as the combination of all other tropical ecosystems. Vegetation photosynthesis contributes more than ecosystem respiration to IAV of the global net land carbon flux, but large uncertainties remain on the contribution of fires and other disturbance fluxes. Climatic variations are the major drivers to the IAV of net land carbon flux. Although debate remains on whether the dominant driver is temperature or moisture variability, their interaction,that is, the dependence of carbon cycle sensitivity to temperature on moisture conditions, is emerging as key regulators of the carbon cycle IAV. On timescales from the interannual to the centennial, global carbon cycle variability will be increasingly contributed by northern land ecosystems and oceans. Therefore, both improving Earth system models (ESMs) with the progressive understanding on the fast processes manifested at interannual timescale and expanding carbon cycle observations at broader spatial and longer temporal scales are critical to better prediction on evolution of the carbon–climate system.

Largely underestimated carbon emission from land use and land cover change in the conterminous United States - Zhen Yu; Chaoqun Lu; Hanqin Tian; Josep G. Canadell (Global Change Biology, 2019)
Carbon (C) emission and uptake due to land use and land cover change (LULCC) are the most uncertain term in the global carbon budget primarily due to limited LULCC data and inadequate model capability (e.g., underrepresented agricultural managements). We take the commonly used FAOSTAT‐based global Land Use Harmonization data (LUH2) and a new high‐resolution multisource harmonized national LULCC database (YLmap) to drive a land ecosystem model (DLEM) in the conterminous United States. We found that recent cropland abandonment and forest recovery may have been overestimated in the LUH2 data derived from national statistics, causing previously reported C emissions from land use have been underestimated due to the definition of cropland and aggregated LULCC signals at coarse resolution. This overestimation leads to a strong C sink (30.3 ± 2.5 Tg C/year) in model simulations driven by LUH2 in the United States during the 1980–2016 period, while we find a moderate C source (13.6 ± 3.5 Tg C/year) when using YLmap. This divergence implies that previous C budget analyses based on the global LUH2 dataset have underestimated C emission in the United States owing to the delineation of suitable cropland and aggregated land conversion signals at coarse resolution which YLmap overcomes. Thus, to obtain more accurate quantification of LULCC‐induced C emission and better serve global C budget accounting, it is urgently needed to develop fine‐scale country‐specific LULCC data to characterize the details of land conversion.

Global soil nitrous oxide emissions since the preindustrial era estimated by an ensemble of terrestrial biosphere models: Magnitude, attribution, and uncertainty - Hanqin Tian; Jia Yang; Rongting Xu; Chaoqun Lu; Josep G. Canadell; Eric A. Davidson; Robert B. Jackson; Almut Arneth; Jinfeng Chang; Philippe Ciais; Stefan Gerber; Akihiko Ito; et al. (Global Change Biology, 2019)
Our understanding and quantification of global soil nitrous oxide (N 2 O) emissions and the underlying processes remain largely uncertain. Here, we assessed the effects of multiple anthropogenic and natural factors, including nitrogen fertilizer (N) application, atmospheric N deposition, manure N application, land cover change, climate change, and rising atmospheric CO 2 concentration, on global soil N 2 O emissions for the period 1861–2016 using a standard simulation protocol with seven process‐based terrestrial biosphere models. Results suggest global soil N 2 O emissions have increased from 6.3 ± 1.1 Tg N 2 O‐N/year in the preindustrial period (the 1860s) to 10.0 ± 2.0 Tg N 2 O‐N/year in the recent decade (2007–2016). Cropland soil emissions increased from 0.3 Tg N 2 O‐N/year to 3.3 Tg N 2 O‐N/year over the same period, accounting for 82% of the total increase. Regionally, China, South Asia, and Southeast Asia underwent rapid increases in cropland N 2 O emissions since the 1970s. However, US cropland N 2 O emissions had been relatively flat in magnitude since the 1980s, and EU cropland N 2 O emissions appear to have decreased by 14%. Soil N 2 O emissions from predominantly natural ecosystems accounted for 67% of the global soil emissions in the recent decade but showed only a relatively small increase of 0.7 ± 0.5 Tg N 2 O‐N/year (11%) since the 1860s. In the recent decade, N fertilizer application, N deposition, manure N application, and climate change contributed 54%, 26%, 15%, and 24%, respectively, to the total increase. Rising atmospheric CO 2 concentration reduced soil N 2 O emissions by 10% through the enhanced plant N uptake, while land cover change played a minor role. Our estimation here does not account for indirect emissions from soils and the directed emissions from excreta of grazing livestock. To address uncertainties in estimating regional and global soil N 2 O emissions, this study recommends several critical strategies for improving the process‐based simulations.

Carbon cycle responses of semi‐arid ecosystems to positive asymmetry in rainfall - Vanessa Haverd; Anders Ahlström; Benjamin Smith; Josep G. Canadell (Global Change Biology, 2017)
Recent evidence shows that warm semi‐arid ecosystems are playing a disproportionate role in the interannual variability and greening trend of the global carbon cycle given their mean lower productivity when compared with other biomes (Ahlström et al . 2015 Science , 348, 895). Using multiple observations (land‐atmosphere fluxes, biomass, streamflow and remotely sensed vegetation cover) and two state‐of‐the‐art biospheric models, we show that climate variability and extremes lead to positive or negative responses in the biosphere, depending on vegetation type. We find Australia to be a global hot spot for variability, with semi‐arid ecosystems in that country exhibiting increased carbon uptake due to both asymmetry in the interannual distribution of rainfall (extrinsic forcing), and asymmetry in the response of gross primary production ( GPP ) to rainfall change (intrinsic response). The latter is attributable to the pulse‐response behaviour of the drought‐adapted biota of these systems, a response that is estimated to be as much as half of that from the CO 2 fertilization effect during 1990–2013. Mesic ecosystems, lacking drought‐adapted species, did not show an intrinsic asymmetric response. Our findings suggest that a future more variable climate will induce large but contrasting ecosystem responses, differing among biomes globally, independent of changes in mean precipitation alone. The most significant changes are occurring in the extensive arid and semi‐arid regions, and we suggest that the reported increased carbon uptake in response to asymmetric responses might be contributing to the observed greening trends there.

Anthropogenic‐driven rapid shifts in tree distribution lead to increased dominance of broadleaf species - Jordi Vayreda; Jordi Martinez‐Vilalta; Marc Gracia; Josep G. Canadell; Javier Retana (Global Change Biology, 2016)
Over the past century, major shifts in the geographic distribution of tree species have occurred in response to changes in land use and climate. We analyse species distribution and abundance from about 33 000 forest inventory plots in Spain sampled twice over a period of 10–12 years. We show a dominance of range contraction (extinction), and demographic decline over range expansion (colonization), with seven of 11 species exhibiting extinction downhill of their distribution. Contrary to expectations, these dynamics are not always consistent with climate warming over the study period, but result from legacies in forest structure due to past land use change and fire occurrence. We find that these changes have led to the expansion of broadleaf species (i.e. family Fagaceae ) over areas formerly dominated by conifer species (i.e. family Pinaceae ), due to the greater capacity of the former to respond to most disturbances and their higher competitive ability. This recent and rapid transition from conifers to broadleaves has important implications in forest dynamics and ecosystem services they provide. The finding raises the question as to whether the increasing dominance of relatively drought‐sensitive broadleaf species will diminish resilience of Mediterranean forests to very likely drier conditions in the future.

Estimating cropland carbon mitigation potentials in China affected by three improved cropland practices - Fei Lun; Josep G. Canadell; Lu He; Bo Yang; Mou-cheng Liu; Zheng Yuan; Mi Tian; Jun-guo Liu; Wen-hua Li (Journal of Mountain Science, 2016)

Effects of climate extremes on the terrestrial carbon cycle: concepts, processes and potential future impacts - Dorothea Frank; Markus Reichstein; Michael Bahn; Kirsten Thonicke; David Frank; Miguel D. Mahecha; Pete Smith; Marijn van der Velde; Sara Vicca; Flurin Babst; Christian Beer; Nina Buchmann; et al. (Global Change Biology, 2015)
Extreme droughts, heat waves, frosts, precipitation, wind storms and other climate extremes may impact the structure, composition and functioning of terrestrial ecosystems, and thus carbon cycling and its feedbacks to the climate system. Yet, the interconnected avenues through which climate extremes drive ecological and physiological processes and alter the carbon balance are poorly understood. Here, we review the literature on carbon cycle relevant responses of ecosystems to extreme climatic events. Given that impacts of climate extremes are considered disturbances, we assume the respective general disturbance‐induced mechanisms and processes to also operate in an extreme context. The paucity of well‐defined studies currently renders a quantitative meta‐analysis impossible, but permits us to develop a deductive framework for identifying the main mechanisms (and coupling thereof) through which climate extremes may act on the carbon cycle. We find that ecosystem responses can exceed the duration of the climate impacts via lagged effects on the carbon cycle. The expected regional impacts of future climate extremes will depend on changes in the probability and severity of their occurrence, on the compound effects and timing of different climate extremes, and on the vulnerability of each land‐cover type modulated by management. Although processes and sensitivities differ among biomes, based on expert opinion, we expect forests to exhibit the largest net effect of extremes due to their large carbon pools and fluxes, potentially large indirect and lagged impacts, and long recovery time to regain previous stocks. At the global scale, we presume that droughts have the strongest and most widespread effects on terrestrial carbon cycling. Comparing impacts of climate extremes identified via remote sensing vs. ground‐based observational case studies reveals that many regions in the (sub‐)tropics are understudied. Hence, regional investigations are needed to allow a global upscaling of the impacts of climate extremes on global carbon–climate feedbacks.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Residential energy consumption and associated carbon emission in forest rural area in China: A case study in Weichang County - Fei Lun; Josep G. Canadell; Zhong-qi Xu; Lu He; Zheng Yuan; Dan Zhang; Wen-hua Li; Mou-cheng Liu (Journal of Mountain Science, 2014)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Jordi Vayreda; Marc Gracia; Josep G. Canadell; Javier Retana (Ecosystems, 2012)

Quantifying, Understanding and Managing the Carbon Cycle in the Next Decades - Josep G. Canadell; Philippe Ciais; Peter Cox; Martin Heimann (Climatic Change, 2004)

Nonlinearities, Feedbacks and Critical Thresholds within the Earth's Climate System - José A. Rial; Roger A. Pielke; Martin Beniston; Martin Claussen; Josep Canadell; Peter Cox; Hermann Held; Nathalie de Noblet-Ducoudré; Ronald Prinn; James F. Reynolds; José D. Salas (Climatic Change, 2004)

Elevated CO2, litter chemistry, and decomposition: a synthesis - Richard J. Norby; M. Francesca Cotrufo; Philip Ineson; Elizabeth G. O’Neill; Josep G. Canadell (Oecologia, 2001)

Mediterranean terrestrial ecosystems: research priorities on global change effects - SANDRA LAVOREL; JOSEP CANADELL; SERGE RAMBAL; JAUME TERRADAS (Global Ecology and Biogeography, 1998)